THE ESSENCE AND IMPORTANCE OF RESEARCH COMPETENCE IN THE ACTIVITY OF A HIGH SCHOOL TEACHER - Drobina, L. M; Halahdina, A.; Gerasym, L.; Migalchan, A.; Migalchan, T. (My University, 2021)
The modern system of higher education requires aising the quality of professional training of specialists at all levels, as well as of the teachers at higher educational institutions. Of particular importance is the modernization of the content, methods and forms of training of graduates of higher educational institutions, able to be competent in the field of scientific and pedagogical activity. The process of preparing future professors requires the formation of research competence in them, the value of which is to develop the creative potential of the individual, improve skills and ways of self-development, elevated professional status.
Keywords: education; teacher; competence